Adults’ End-of-Life Wishes Beyond Clinical and Legal Tools: Scoping Review Protocol - Coupat, Clémence; Breton-Piette, Alexandra; Sergerie-Richard, Sophie; Turnbull, Tania; Leon Palomino, Cécilia; Allard, Émilie (Science of Nursing and Health Practices / Science infirmière et pratiques en santé, 2025)
Introduction: Research on end-of-life wishes (EoLW) primarily focuses on the elderly or ill individuals, limiting reflection to specific moments within life trajectories. Drawing on Patterson and Hazelwood (2020), this article proposes 4 dimensions of EoLW: medical care, legal considerations, personal priorities, and socio-spiritual well-being. While numerous knowledge syntheses explore EoLW, they primarily focus on the first 2 dimensions, overlooking aspects that are nonetheless essential to true person-centered end-of-life planning. Objective: To map the extent and nature of knowledge on personal priorities and socio-spiritual well-being dimensions of EoLW and to identify trends, gaps, and implications for research and practice. Method: This scoping review follows the 6-step methodology of Levac et al. (2010) and queries scientific (CINAHL Complete, Érudit, MEDLINE, PsycINFO, Social Sciences Abstracts, Social Work Abstracts and Web of science) and grey literature (Dissertations & Theses Global and Sociological Abstracts) databases. Literature published from 2015 onwards, in English or French, will be systematically identified and selected through an independent double anonymous review process. Discussion and Research Spin-offs: We will identify the contexts in which these 2 dimensions are operationalized, the research methodologies used and any knowledge gaps in the current state of research. Engagement with key stakeholders in the 6th stage of this scoping review will facilitate the synthesis of critical insights to better inform practice, influence policy development, and guide future research.